(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
This article highlights the ranking of areas by socio-economic indicators. For a full study, we defined the concepts of the regional tourism market and combined 4 regions: Volyn, Rivne, Lviv and Ternopil into the Western Regional Tourist Region (ZRTR). Each region was characterized by the following indicators: population, average wage, number of tourists served, number of collective facilities, number of hotels and similar recreation facilities, number of sanatoriums and recreation centers. The studies were conducted using data from the General Statistics Office of each area. They charted and identified the most optimal area for tourism market development. Next, they built a table where the colors indicated the areas by their position. Lviv region took 4th place, followed by Volyn region - 3, Rivne region - 2, and Ternopil – 1. That is, the Lviv region received the highest rating. Next, we color-coded the rating of Western Regional Tourism Market areas: the brighter the color, the better the tourism market is compared to other areas. Areas that have been downgraded should pay attention to local regulation and improve their tourism potential by using different development strategies and modernization projects. Introduction. Studying the tourist market of the Volyn region and its features: structure, functions, types and other, in my opinion, for a deeper study it is worthwhile to analyze the ranking of socio-economic indicators of the Western Regional Tourism Market (ZRTR). Our study covers 4 areas: Volyn, Ternopil, Lviv, and Rivne. With the help of this research we will derive a certain rating of areas for the development of the tourist services market and will be able to determine the most optimal area for tourism development in general. The purpose of the article. The main purpose of this study is to analyze the ranking of socio-economic indicators of the Western Regional Tourism Market Results. Lviv region took 4th place, followed by Volyn region - 3, Rivne region - 2, and Ternopil – 1. That is, the Lviv region received the highest rating. Next, we color-coded the rating of Western Regional Tourism Market areas: the brighter the color, the better the tourism market is compared to other areas. Areas that have been downgraded should pay attention to local regulation and improve their tourism potential by using different development strategies and modernization projects. Conclusions. Table 1 shows the ranking positions of the LRTF regions by socio-economic indicators. The lighter the color and the lower the value of the rating, the worse the tourist position of the area compared to the other. It follows that the best situation and the most optimal area for tourism development is the Lviv region. The situation is slightly worse in Volyn and Rivne regions. But not so successful in the development of tourism is the Ternopil region, which requires many recommendations for improving the tourist status of the region. Therefore, in the perspective of further research it is necessary to focus on, in fact, the methods of regional and local state regulatory bodies, namely the development of the tourist market in the regions. In order to modernize and stimulate the development of the tourism industry in areas that have received low marks in the RDA rating study, it is necessary to identify priority areas of work and find those tourism projects and development strategies that would be most optimal in a given region